Anchoring of phthalic acid on MgO(100) - Kataev, Elmar; Fromm, Lukas; Tariq, Quratulain; Wechsler, Daniel; Williams, Federico J.; Tsud, Nataliya; Franchi, Stefano; Steinrück, Hans-Peter; Görling, Andreas; Lytken, Ole (Surface Science, 2022)
Carboxylic acids are often used to anchor large organic molecules to oxide surfaces. To understand the mechanism of this anchoring we have studied the temperature and coverage-dependent adsorption and reactions of phthalic acid on MgO(100) by a combination of X-ray photoelectron spectroscopy, near-edge X-ray absorption, UV photoelectron spectroscopy and density-functional theory. At 110 K, phthalic acid partly deprotonates on MgO(100) at low coverage and forms a dicarboxylate species. At higher coverage, the fraction of intact phthalic acid increases to a larger extent than that of the deprotonated species. Subsequent annealing of these mixed structures results in the full conversion of the remaining intact acid groups to carboxylate, that is, doubly deprotonated phthalic acid, at 250 K. Depending on coverage, the carboxylate-bonded species remain stable up to 500 – 600 K. Above this temperature, the molecules decompose and desorb as fragments, leaving only a small carbon residue behind on the surface.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Magnesium oxide; Organic thin films; Phthalic acid; X-ray photoelectron spectroscopy